Bridging the gap: Evidence-based practice guidelines for sports nutritionists - Ritson, Alex J.; Hearris, Mark A.; Bannock, Laurent G. (Frontiers in Nutrition, 2023)
Evidence-based practice is a systematic approach to decision-making developed in the 1990s to help healthcare professionals identify and use the best available evidence to guide clinical practice and patient outcomes amid a plethora of information in often challenging, time-constrained circumstances. Today's sports nutrition practitioner faces similar challenges, as they must assess and judge the quality of evidence and its appropriateness to their athlete, in the often chaotic, time-pressed environment of professional sport. To this end, we present an adapted version of the evidence-based framework to support practitioners efficiently and effectively navigate their way through the deluge of information and guide their recommendations to athletes, whilst also reflecting on their practice experience and skills as evidence-based practitioners; thus, helping to bridge the gap between science and practice in sport and exercise nutrition.